O OBOWIĄZYWANIU ZASADY KONTRADYKTORYJNOŚCI W POSTĘPOWANIU NIEPROCESOWYM: PRZYCZYNEK DO DYSKUSJI - Misztal-Konecka, Joanna (Zeszyty Prawnicze, 2016)
The Adversarial Principle in Non-litigious Proceedings: a Contribution to the Discussion Summary The adversarial principle has been applicable in Polish non-litigious proceedings since 1964, when the provisions for litigious and non-litigious proceedings in Polish civil law were integrated in one civil code, and later when its procedural law was fundamentally revised and amended. Prior to this change, the applicable provisions were defined in the 1945 Code for non-litigious proceedings, which did not admit the adversary system, viz. the principle that the parties to proceedings collect evidence and produce witnesses, while the court merely assists and supervises. There are only two situations in which under current Polish civil law the inquisitorial system may supersede the adversary ststem. The two exceptions are: 1) when ex officio proceedings may be initiated on the grounds of a legislative act; and 2) when it is in the public interest to initiate an ex officio inquiry.